Employee Performance Optimization - Haikal, Muhammad; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this study was to determine and analyze the influence of transformational leadership and work climate on Employee Performance mediated by Work Motivation at the North Sumatra Regional Disaster Management Agency (BPDB) Office. This research was conducted at the North Sumatra Regional Disaster Management Agency (BPDB) Office. The type of research is associative quantitative. The sample in this study was 127 ASN and honorary employees at the North Sumatra Regional Disaster Management Agency (BPDB) Office. The sampling technique in this study used random sampling technique from the entire population of 186 people. The results showed that Transformational Leadership has a significant influence on Employee performance as indicated by the T-Statistic value of 23.039> 1.96 and the P Value of 0.000 <0.05. On the influence of Work Climate on Employee work, the T-Statistic value data was obtained 1.251 <1.96 and the P-Value value of 0.213 <0.05 or there was no influence of work climate on employee performance. Transformational Leadership Style has a significant effect on Employee Work Motivation with a T-Statistic value of 17.128> 1.96 with a P-Value of 0.001 <0.05. Work Climate has a significant effect on Employee Work Motivation. This can be seen from the results of the T-Statistic values of 67.389> 1.96 with a P-Value of 0.000 <0.05. On the influence of Work Motivation on Employee performance, a T-Statistic value of 19.409 <1.96 with a P-Value of 0.000> 0.05 is obtained, which means that Work Motivation does not have a significant effect on the performance of Employees of the North Sumatra Regional Disaster Management Agency (BPDB) Office. In the indirect effect, the results show that Work Motivation has a role as an intervention variable in explaining the relationship between Transformational Leadership and Work Climate with Employee performance. This shows that improvements in Transformational Leadership and Work Climate can increase Work Motivation, which ultimately contributes to improving Employee performance at the North Sumatra Regional Disaster Management Agency (BPDB) Office.